(untitled) (Journal of Informatics Education and Research, 2025)
This paper examines the Shivalinga (Śivaliṅga) and Jyotirlinga (Jyotirliṅga) as two intertwined yet distinct expressions of Lord Shiva in Hindu tradition. Through historical, theological, and architectural lenses, we explore how the aniconic form of the linga evolved and how the concept of the twelve sacred Jyotirlingas emerged as ‘flames of divinity’ across India. Drawing on classical Sanskrit texts – including the Shiva Purana and Linga Purana – as well as scholarly interpretations, the analysis examines of the structural attributes of lingas in temples and the spiritual narratives that distinguish Jyotirlingas. The study compares regional variations and chronicles how linga worship has spanned from ancient Indus Valley traces to medieval temple networks. Traditional interpretations of the linga as a cosmic pillar and symbol of creation are compared with modern scientific perspectives, such as archaeological findings and the metallurgical marvel of mercury lingas.